2016
DOI: 10.1152/jn.00553.2016
|View full text |Cite
|
Sign up to set email alerts
|

Normal correspondence of tectal maps for saccadic eye movements in strabismus

Abstract: The superior colliculus is a major brain stem structure for the production of saccadic eye movements. Electrical stimulation at any given point in the motor map generates saccades of defined amplitude and direction. It is unknown how this saccade map is affected by strabismus. Three macaques were raised with exotropia, an outwards ocular deviation, by detaching the medial rectus tendon in each eye at age 1 mo. The animals were able to make saccades to targets with either eye and appeared to alternate fixation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Other studies in strabismic monkeys using SC electrical stimulation have also shown that there were influences on strabismic angle during electrical stimulation. 10,22,23 Our analysis of the stimulation data indicated that the strabismus angle changes were a consequence of disconjugate saccades and also disconjugate postsaccadic drift. 7 We hypothesized that the disconjugate postsaccadic drift could be the consequence of stimulating a population of vergence (misalignment in the case of strabismic monkeys) cells within the SC.…”
mentioning
confidence: 80%
“…Other studies in strabismic monkeys using SC electrical stimulation have also shown that there were influences on strabismic angle during electrical stimulation. 10,22,23 Our analysis of the stimulation data indicated that the strabismus angle changes were a consequence of disconjugate saccades and also disconjugate postsaccadic drift. 7 We hypothesized that the disconjugate postsaccadic drift could be the consequence of stimulating a population of vergence (misalignment in the case of strabismic monkeys) cells within the SC.…”
mentioning
confidence: 80%
“…Eye muscle surgery has been used to experimentally induce strabismus in monkeys for many years. 10,11,[21][22][23][38][39][40][41][42][43][44] Nonetheless, one might wonder whether the pattern strabismus in these animals might be due to an abnormal pulling direction for the medial rectus muscles. To further test this possibility, we performed two additional analyses: First, we recorded 15 medial rectus motoneurons from monkey XT1 and plotted the preferred directions using the same procedure described above for the NPH neurons.…”
Section: Consideration Of Alternative Explanationsmentioning
confidence: 99%
“…For a subset of patients, the horizontal and vertical misalignments vary with eye position along the orthogonal axis 1. When the horizontal and vertical eye positions are plotted simultaneously in these patients, the misalignments form a pattern that often resembles the letters “A” or “V.”26 Thus, this condition is referred to as “pattern strabismus.”…”
mentioning
confidence: 99%
“…Numerous studies employing nonhuman primate models of the infantile strabismus syndrome have shown that, when binocular vision is disturbed for a prolonged period in infancy, both visual and oculomotor areas of the brain develop abnormally 7,8. Most of these monkeys develop at least a mild “A” or “V” pattern, and some show a strong pattern strabismus 3,5,6. In human patients, pattern strabismus is typically described, and treated, as overaction or underaction of the oblique muscles 1,9.…”
mentioning
confidence: 99%
See 1 more Smart Citation